Incidence of tuberculosis and associated mortality in a cohort of human immunodeficiency virus-infected children initiating antiretroviral therapy - Nicolas Salvadori (2018)
© The Author 2017. Background. We assessed the incidence of tuberculosis, risk factors for tuberculosis, and the contribution of tuberculosis on mortality in a large cohort of human immunodeficiency virus (HIV)-infected children < 15 years of age initiating first-line antiretroviral therapy (ART) between 1999 and 2012 in Thailand, one of the 22 high tuberculosis burden countries. Methods. A physician reviewed and classified tuberculosis cases. Incidence was the number of children with incident tuberculosis, defined as a first or recurrent tuberculosis diagnosis > 30 days after ART initiation, divided by the total person-years of follow- up (PYFU). Risk factors for incident tuberculosis were identified using Fine and Gray's competing risks models, with death from other causes treated as a competing event, and risk factors for death were identified using Cox models. Results. At ART initiation, 670 children (55% female) had a median age of 6.4 years (interquartile range, 2.0-9.6), body mass index-for-age z-score -0.8 (-1.9 to 0.0), HIV ribonucleic acid viral load 5.1 log10 copies/mL (4.6-5.6), and CD4 9% (3-17). Median duration of follow-up was 7.7 years. Tuberculosis incidence was 7 per 1000 PYFU (95% confidence interval [CI], 5-11) and decreased with ART duration. Lower age-adjusted hemoglobin, hematocrit, and CD4 at ART initiation were associated with a higher risk of incident tuberculosis. Of the 30 incident tuberculosis cases, 9 died. Diagnosis of incident tuberculosis was associated with mortality (unadjusted hazard ratio = 10.2, 95% CI = 4.8-21.5, P < .001 and adjusted hazard ratio = 5.4, 95% CI = 2.5-11.7, P < .001). Conclusions. Incident tuberculosis was strongly associated with mortality. CD4 counts or hemoglobin or hematocrit levels may prompt clinicians to consider a possible tuberculosis infection.